1997
DOI: 10.1021/jp972422+
|View full text |Cite
|
Sign up to set email alerts
|

Free Electron Attachment and Rydberg Electron Transfer to NF3Molecules and Clusters

Abstract: Free electron attachment in the energy range 0−10 eV and Rydberg electron transfer (RET) to NF3 molecules, NF3 clusters, and NF3/Ar clusters are studied by means of negative ion mass spectrometry. The experimental results are compared with density functional theory (DFT) calculations. In the free electron experiment gas-phase NF3 generates the dissociative attachment (DA) products F-, F2 -, and NF2 - appearing from a broad resonance around 2 eV, in agreement with an earlier beam experiment. The most abundant f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
39
1

Year Published

2001
2001
2009
2009

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 30 publications
5
39
1
Order By: Relevance
“…The electron-beam experiment of Ruckhaberle et al 39 with NF 3 clearly showed a zero-energy resonance for the production of F − , which grew as the NF 3 temperature was TABLE I. Electron attachment rate constants k a for NF 3 obtained with the FALP apparatus and the new HT-FALP apparatus in the present work. The experimental uncertainty is Ϯ25% except for the 300 K datum ͑Ϯ50%͒.…”
Section: Resultsmentioning
confidence: 49%
See 2 more Smart Citations
“…The electron-beam experiment of Ruckhaberle et al 39 with NF 3 clearly showed a zero-energy resonance for the production of F − , which grew as the NF 3 temperature was TABLE I. Electron attachment rate constants k a for NF 3 obtained with the FALP apparatus and the new HT-FALP apparatus in the present work. The experimental uncertainty is Ϯ25% except for the 300 K datum ͑Ϯ50%͒.…”
Section: Resultsmentioning
confidence: 49%
“…G3 energies for molecules needed in the calculation of reaction energetics are tabulated in Table II. G3 and experimental [39][40][41][42] electron affinities are also listed in Table II. With all data included, the activation energies determined with the FALP and HT-FALP from Arrhenius fits ͑Fig. 6͒ are 0.22 and 0.25 eV, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the use of NF 3 can also prevent carbon contamination and create only minor crystal damage. Recently, many works have focused on the NF 3 or NF 3 K system [24][25][26]. For example, Nike and his coworkers [25] studied free electron attachment and Rydberg ET to NF 3 molecules and clusters; however, the study of NF 3 /NF 3 C coupling system has not been done.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, many works have focused on the NF 3 or NF 3 K system [24][25][26]. For example, Nike and his coworkers [25] studied free electron attachment and Rydberg ET to NF 3 molecules and clusters; however, the study of NF 3 /NF 3 C coupling system has not been done. One of the goals of the present article is to theoretically study the structures, properties, and the ET reactivity of NX 3 /NX 3 C (XZH, F) systems, and to discuss the contact distance dependence of various ET kinetics parameters such as the activation energy, the coupling matrix element and the ET rate.…”
Section: Introductionmentioning
confidence: 99%